Efektivitas Carboxymethyl Cellulose (CMC) dan Gula terhadap Kadar Serat Fruit Leather Siwalan (Borassus flabellifer) - Ulfa Maulida Farid; Ahmad Mundzir Romdhani; Nur Roudatul Jannah (Institut Agama Islam Negeri Kerinci, 2025)
Until now, the utilization of siwalan fruit is limited to direct consumption of the fruit. Siwalan fruit processed into siwalan fruit leather can be an alternative food with high fiber. Stabilizers are needed to maintain the physical texture of siwalan fruit leather in order to obtain the appropriate quality. One of them is by adding a concentration of Carboxymethyl Cellulose (CMC) and sugar. This study aims to determine the effectiveness of Carboxymethyl Cellulose (CMC) and sugar on the fiber content of siwalan fruit leather (Borassus flabellifer). The fiber content test of siwalan fruit leather used a gravimetric test. The concentration of added sugar and CMC in siwalan fruit leather consisted of 4 treatments and 6 repetitions, namely P1: CMC 0% SUGAR 10%, P2: CMC 0.5% SUGAR 10%, P3: CMC 1.0% SUGAR 15%, P4: CMC 0.5% SUGAR 20%. The addition of Carboxymethyl Cellulose (CMC) and sugar has a significant effect on increasing the fiber content of fruit leather siwalan (Borassus flabellifer) with a Sig. value of 0.001 <0.05. The higher the concentration of Carboxymethyl Cellulose (CMC), the fiber content will also increase. The higher the concentration of sugar given, the more it will provide an increase in terms of aroma, taste and texture of fruit leather.